Primary retroperitoneal lymphangioleiomyomatosis in a postmenopausal woman: a case report and review of the literature. Issue 2 (1st February 2007) - Kebria, M.; Black, D.; Borelli, C.; Modica, I.; Hensley, M.; Chi, D. S.
Abstract : Lymphangioleiomyomatosis (LAM) is a rare progressive disease of unknown etiology that typically affects women of childbearing age. It is characterized by an abnormal proliferation of smooth muscle cells causing gradual obstruction of small airways, frequently resulting in respiratory failure and death. While LAM is predominantly a lung disorder, we report a case of retroperitoneal LAM in a patient who had no evidence of pulmonary involvement. A 59-year-old female presented with postmenopausal bleeding and no other complaints. She was found to have a low attenuation retroperitoneal mass on abdominal and pelvic computed tomography (CT) scan suspicious for lymphoma. CT-guided biopsy was nondiagnostic. Laparoscopic resection of some of the enlarged retroperitoneal lymph nodes confirmed the diagnosis of LAM. This case is an atypical presentation of LAM. The disease typically presents in premenopausal women, with the initial site of involvement being the lungs and mediastinum. In rare cases, such as this of extrapulmonary LAM, patients typically present with a palpable abdominal mass, abdominal pain, or chylous ascites. As in our case, radiographic findings can mimic malignancies such as lymphoma. Laparoscopic lymph node biopsy is a valuable tool in these situations of diagnostic dilemma